Impact of MDM2 promoter SNP55 (rs2870820) on risk of endometrial and ovarian cancer. (19th May 2021) - Helwa, Reham; Gansmo, Liv B.; Bjørnslett, Merete; Halle, Mari Kyllesø; Werner, Henrica M. J.; Romundstad, Pål; Hveem, Kristian; Vatten, Lars; Dørum, Anne; Lønning, Per E.; Knappskog, Stian
Abstract: Background: While large GWAS analyses have not found convincing associations between MDM2 promoter SNP55 and gynaecological cancers, SNP55 is in linkage disequilibrium with two other functional SNPs in the same promoter, likely to obscure associations between single SNPs and cancer risk. Here, we assessed the impact of SNP55 on risk of endometrial and ovarian cancer, including sub-analyses stratified for other functional SNPs in the region. Material and methods: Using a custom LightSNiP assay, we genotyped SNP55 in two large hospital-based cohorts of patients with ovarian (n = 1, 332) and endometrial (n = 1, 363) cancer and compared genotypes to healthy female controls (n = 1, 858). Results: Among individuals harbouring the SNP309TT genotype, the minor SNP55T-allele was associated with a reduced risk of endometrial (dominant model: OR = 0.63; CI = 0.45–0.88; p = 0.01). Regardless of the genotype in neighbouring SNPs, the SNP55T-allele was also associated with a reduced risk of endometrial cancer before 50 years of age (dominant model: OR = 0.56; CI = 0.34–0.90; p = 0.02). No association between SNP55 status and ovarian cancer risk was observed. Conclusions: MDM2 SNP55T-allele may correlate with reduced risk for endometrial cancer in a SNP309T-, but not SNP309G, context.